KESESUAIAN RESEP DENGAN STANDAR PELAYANAN MEDIS DAN FORMULARIUM JAMKESMAS PADA PASIEN RAWAT JALAN JAMKESMAS - Dian Medisa; Sulanto Saleh Danu; Rustamaji Rustamaji (Universitas Islam Indonesia, 2015)
Health is rights of every human. In Indonesia, poor people had difficulty to access health services. Therefore government creates a program called “Jamkesmas” which based on DRGs (Diagnosis Related Groups) to improve quality of health services. Physicians should prescribe medicines according to the diagnosis and Jamkesmas formulary. The compliance between prescription with Standard Treatment Guidelines (STGs) and Jamkesmas formulary is a must. The aim of this research was to know the prescriptions compliance to STGs and Jamkesmas formulary. This research was observational study using prescriptions of Jamkesmas’s outpatients . Furthermore, qualitative data with in-depth interviews was used to further analysis. Quantitative data were calculated by using drug use indicators for the percentage of prescriptions compliance. The percentage of prescriptions compliance with STGs in each of 10 diseases in once of hospital in Daerah Istimewa Yogyakarta (Hospital X), started from 24.3% in CHF to 82% in DM diseases, whereas prescriptions compliance with Jamkesmas Formulary was started from 49% in vertigo to 96% in hypertension diseases. Average number of drugs per prescription was 2.7 and the most of drugs (85.7%) were prescribed by its generic names; 23.3% of prescriptions contained antibiotic and 22.0% contained of injectable drug. Percentage of drugs prescribed from essential medicines list was 76.7%. The prescriptions of 10 diseases were not fully compliance to Standard Treatment Guidelines and Jamkesmas formulary.